Direct Observation of Reverse Magnetic Domain and Magnetic Domain Wall Motion in Nd-Fe-B Magnet at High Temperature by Lorentz Microscop. Issue 3 (2016) - Suzuki, Toshimasa; Kawahara, Koichi; Suzuki, Masaya; Takagi, Kenta; Ozaki, Kimihiro
ABSTRACT: We conducted the in-situ observations of the magnetic domain structure change in Nd-Fe-B magnets at high temperature by transmission electron microscopy (TEM) / Lorentz microscopy with applying an external magnetic field. Prior to observation, a thin foil was magnetized by an external magnetic field of 2.0 T to almost saturation, then the magnetic domain structures were observed by the Fresnel mode with in-situ heating. At 225°C, reverse magnetic domains were found to generate in the thin foil sample without applying an external magnetic field. When we applied a magnetic field on the same direction to the pre-magnetization direction at 225°C, one magnetic domain wall was pinned by a grain boundary and the other magnetic domain wall moved. As the results, the reverse magnetic domain shrank then annihilated. When we cut the applied magnetic field, the reverse magnetic domain generated at almost the same location. On the other hand, when we applied a magnetic field to the foils in the opposite direction, the reverse domain started to grow, i.e., magnetic domain walls started to move. The observation results of the shrink or growth of the reverse domain showed that the pinning effect of grain boundary against domain wall motion would be different depending on the applied magnetic field direction. Moreover, domain walls was observed to be pinned by grain boundaries at elevated temperature, so that the coercivity of Nd-Fe-B magnet would occur by pinning mechanism.